Potato consumption and risk of colorectal and pancreatic cancer. The Norwegian Women and Cancer cohort and the HELGA cohort. - Åsli, Lene Angell (UiT The Arctic University of Norway, 2016)
The papers 2 and 3 of this thesis are not available in Munin. Paper 2: Åsli, L. A., Olsen, A., Braaten, T., Lund, E., Skeie, G.: "Potato consumption and risk of colorectal cancer in the Norwegian Women and Cancer cohort". (Manuscript). Paper 3: Åsli, L. A., Braaten, T., Olsen, A., Tjønneland, A., Overvad, K., Nilsson, L. M., Renström, F., Lund, E., Skeie, G.: "Potato consumption and risk of pancreatic cancer in the HELGA cohort". (Manuscript). Summary The present work includes participants from two cohorts: The Norwegian Women and Cancer (NOWAC) study (paper 1 and 2) and the HELGA study (paper 3). The NOWAC Study is a population-based prospective cohort study that started data collection in 1991, and consists of more than 172,000 women. The HELGA study is a population-based Scandinavian cohort, consisting of 119,978 men and women from: NOWAC, The Northern Sweden Health and Disease Study Cohort and the Danish Diet, Cancer and Health Study. Potatoes are the world`s largest food crop after wheat, rice and corn. Potatoes are an important source of fiber, niacin, vitamin C, proteins and several minerals. Studies on health effects of potatoes have found associations between potato consumption and cardiometabolic health and several cancers, but the scientific literature on the health effects of potato consumption is scarce and contradictory. Additionally, potatoes have a high glycemic index (GI) and glycemic load (GL), and studies have shown that food with high GI and GL are associated with increased risk of several chronic diseases, such as type 2 diabetes, heart disease and several cancers, including colorectal and pancreatic cancer. The aim of this thesis was to Cross-sectionally investigate what characterises women who eat potatoes (Paper 1), investigate prospectively the association between potato consumption and colorectal cancer risk (Paper 2), and to investigate prospectively the association between potato consumption and pancreatic cancer risk (Paper 3). We found that the high potato consumption group ...